Development Strategy of Kebo Beach Tourist Destination to Increase Marine Tourism Visits in Trenggalek District - Ardiansyah, Johan; Purnomo, Agus (Proceeding International Conference on Religion, Science and Education, 2025)
Kebo Beach is a new tourist destination in Trenggalek District. There are various factors for not achieving the annual visit target. Although it has carried out promotions and procurement of several facilities, in terms of promotion it is still limited and some facilities such as toilets are less well maintained and there is no electricity in general at tourist attractions. The purpose of this research is to analyse the right strategy for the development of Kebo Beach tourist destination in increasing tourist visits in Trenggalek District using SWOT analysis. The method in this study uses descriptive research methods with a quantitative approach. The data collection techniques used in this study were observation, interview and questionnaire techniques. Data analysis techniques in this study using SWOT analysis. The results of this study can determine the development strategy to increase tourist visits based on matrix calculations on Kebo Beach, namely the use of aggressive strategies (growth oriented strategy).